2019
DOI: 10.1007/s00330-019-06300-x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of two commonly used bone age assessment methods to twenty-first century UK children

Abstract: ObjectivesTo assess the effect of secular change on skeletal maturation and thus on the applicability of the Greulich and Pyle (G&P) and Tanner and Whitehouse (TW3) methods.MethodsBoneXpert was used to assess bone age from 392 hand trauma radiographs (206 males, 257 left). The paired sample t test was performed to assess the difference between mean bone age (BA) and mean chronological age (CA). ANOVA was used to assess the differences between groups based on socioeconomic status (taken from the Index of Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
0
28
1
3
Order By: Relevance
“…Van Rijn et al [15] examined the Dutch children's BA and found the GP method usable for BA determination. Al Shamrani et al [17] evaluated the radiographs of 392 patients taken due to trauma in United Kingdom. They observed that there was no significant difference between BA and CA when the GP atlas was used.…”
Section: Discussionmentioning
confidence: 99%
“…Van Rijn et al [15] examined the Dutch children's BA and found the GP method usable for BA determination. Al Shamrani et al [17] evaluated the radiographs of 392 patients taken due to trauma in United Kingdom. They observed that there was no significant difference between BA and CA when the GP atlas was used.…”
Section: Discussionmentioning
confidence: 99%
“…By reading the exam concurrently with the radiologist or as a second read, bounding boxes, markers and probability scores aid the radiologist in the diagnostic process. Many products are on the market and much research has been conducted to demonstrate the performance of these algorithms in comparison to radiologists or a ground truth (level 2) [13,[34][35][36]. However, most of these products cannot be used as a standalone medical device, and it is therefore the accuracy of the combination of the software and radiologist that matters (level 3).…”
Section: Improved Diagnostic Accuracymentioning
confidence: 99%
“…Für Länder mit hohem Einkommen liegen aktuelle Daten von Alshamrani und Offiah (2020) vor [33]. Die Autoren untersuchten 2 unterschiedliche Stadiensysteme für die Handskelettentwicklung an einer englischen Population unterschiedlicher Ethnien im Alter von 2 bis 15 Jahren in der Region Sheffield.…”
Section: Introductionunclassified
“…Alshamrani und Offiah konnten nur für eine der beiden untersuchten Methoden einen Zusammenhang zwischen Skelettalter und SES feststellen. Für die Methode, welche insgesamt besser mit dem chronologischen Alter der Teilnehmer korrelierte, konnte kein Zusammenhang festgestellt werden [33]. Diese Ergebnisse können -ebenso wie die Resultate der gegenständlichen Studie -als Indiz dafür gewertet werden, dass in Ländern mit geringerem sozialen Gefälle kein offensichtlicher Zusammenhang zwischen SES und Skelettalter festzustellen ist.…”
Section: Introductionunclassified